2011
DOI: 10.1071/an11081
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an organic acid mixture and methionine supplements on intestinal morphology, protein and nucleic acids content, microbial population and performance of broiler chickens

Abstract: A study was carried out to investigate the effects of dietary supplementation of an organic acids mixture and two methionine supplements on intestinal morphology, protein and nucleic acids content, microbial population and performance of broiler chickens. Six hundred unsexed day-old Ross 308 broiler chicks were used in a factorial arrangement (3 × 2) based on a completely randomised design by four replicates with 25 chicks in each. Experimental diets consisted of: 0% organic acid mixture + DL-methionine (Treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 30 publications
(33 reference statements)
4
9
0
Order By: Relevance
“…Takahashi and Hiraga (1981) described a reduction in body weight gain in rats dosed with a lower level of 918 mg BHT/ kg/ day for a week better weight gain observed in the group III fed BHT at 130 mg/ kg level might have been due to hepatic microsomal enzyme induction at lower doses. The improvement in LBW are in accord with results of Saki et al (2011), Wickramasinghe et al (2014) and Mohamed et al (2016). Body weight gain of broiler chicks for T4 was significantly (P ≤ 0.05) increased as compared to that of the T1, T2 and T3 during total period (2-36 days) and this is may be due to the more essential oil (EO) of pulicaria undulata aerial parts exhibited activity broiler -performance -antioxidant -blood -manure characteristics.…”
Section: Mineral Determination Of Pulicaria Undulatasupporting
confidence: 90%
See 1 more Smart Citation
“…Takahashi and Hiraga (1981) described a reduction in body weight gain in rats dosed with a lower level of 918 mg BHT/ kg/ day for a week better weight gain observed in the group III fed BHT at 130 mg/ kg level might have been due to hepatic microsomal enzyme induction at lower doses. The improvement in LBW are in accord with results of Saki et al (2011), Wickramasinghe et al (2014) and Mohamed et al (2016). Body weight gain of broiler chicks for T4 was significantly (P ≤ 0.05) increased as compared to that of the T1, T2 and T3 during total period (2-36 days) and this is may be due to the more essential oil (EO) of pulicaria undulata aerial parts exhibited activity broiler -performance -antioxidant -blood -manure characteristics.…”
Section: Mineral Determination Of Pulicaria Undulatasupporting
confidence: 90%
“…Data exposed that PI was increased (P ≤ 0.05) in chicks group T4, at 36 days old. With this regards, (Saki, et al, 2011) reported that the results of broilers index productions were significantly declined by fasting treatments rather than others at 21 and 42 days of age (P ≤ 0.05).…”
mentioning
confidence: 91%
“…For many years, synthetic Met sources have been commonly supplied as either DL-Met or DL-2-hydroxy-4-(methylthio) butanoic acid (DL-HMB) which latter is added in a liquid free acid form or in a dry form as calcium salt. ALIMET ® , 88 % aqueous solution of DL-HMB (Martin-Venegas et al, 2006), is a commercial Met source which used in broiler chicken diets (Saki et al, 2011). It is not an amino acid but rather an organic acid in that it bears a hydroxyl group on α-carbon instead of the amino group found in Met (Yi et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In another study, Esmaeilipour et al (2012) found that supplementation of the diets of broilers with citric acid and xylanase did not have a significant effect on the relative lengths of the small intestine. Saki et al (2011) reported that the addition of 1% level of organic acid mixture significantly increased villus height and crypt depth of broiler chicken. Senköylü et al (2007) found that a combination of different OAs significantly increased the VH in broilers.…”
Section: Intestinal Histomorphologymentioning
confidence: 99%